Monogamy as protection against COVID‐19?: Non‐monogamy stigma and risk (Mis)perception. Issue 3 (27th September 2022) - Conley, Terri D.; Piemonte, Jennifer L.; Shukla, Ishita; Mangla, Ananya; Mateti, Nainika; Tariq, Soha
Abstract: COVID‐19 public health messages largely communicated that Americans were "safer at home." Implicit in this advice are messages about protections ostensibly also offered by monogamy–that having more relationships is always more dangerous than having fewer relationships and that closer relationships are always safer–from a disease transmission perspective–than unfamiliar relationships. These heuristics may have led people to discount other COVID‐19 dangers (such as spending more time with others of unknown infection status) and to ignore COVID‐specific safety measures (such as mask‐wearing, and ventilation). We conducted three studies in which we used experimental vignettes to assess people's perceptions of COVID‐risky targets in monogamous relationships with a close, committed partner versus targets who were described as non‐monogamous with casual partners but relatively COVID‐safe. Participants perceived monogamous‐but‐COVID‐riskier targets as more responsible and safer from COVID‐19. Non‐monogamy stigma seems to extend analogously to COVID‐19 risk. Public health messages that fail to attend to the specifics and nuances of close relationships risk contributing to this stigma and ultimately undermining the goals of reducing the spread of infectious disease.